Toxicity of perfluorinated carboxylic acids for aquatic organisms - Tichý, Miloň; Valigurová, Radka; Cabala, Radomír; Uzlová, Rut; Rucki, Marián (Interdisciplinary toxicology, 2010)
Toxicity of perfluorinated carboxylic acids with carbon chain C(8) to C(12) were tested with oligochaeta Tubifex tubifex. Toxicity was evaluated as the exposure time ET(50) from onset of damage of the oligochaeta in saturated aqueous solutions. The ET(50) fluctuated between 25 and 257 minutes. No statistically significant difference was found among the C(8), C(9) and C(12) acids (ET(50) between 143 and 257 minutes with large standard deviation). The acids with carbon chain C(10) and C(11) induced the effect significantly quicker (25 to 47 minutes). No acute toxicity measured in the three-minute test was observed in any case.
Keywords: effective exposure time; water pollution; perfluorinated carboxylic acids; Tubifex tubifex; acute toxicity